Chronic Kidney Disease - Homoeopathy Helps! (Homoeopathy for All, 2023)
Early kidney disease is a silent  problem, like high blood pressure,  and does not have any symptoms.  People may have CKD but not know  it because they do not feel sick. A  person's glomerular filtration rate  (GFR) is a measure of how well the  kidneys are filtering wastes from  the blood. GFR is estimated from a  routine measurement of creatinine  in the blood. The result is called the  estimated GFR (eGFR). Creatinine is a waste product  formed by the normal breakdown of  muscle cells. Healthy kidneys take  creatinine out of the blood and put it  into the urine to leave the body. When  the kidneys are not working well,  creatinine builds up in the blood. The kidneys maintain the blood  creatinine in a normal range. Creatinine  has been found to be a fairly reliable  indicator of kidney function. Elevated  creatinine level signifies impaired  kidney function or kidney disease.
Keywords: disease; body; blood